2014
DOI: 10.1007/s11011-014-9544-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of social factors on cell death, cerebral plasticity and recovery after stroke

Abstract: Stroke is a serious global health care problem. It is now is the fourth leading cause of death and the primary cause of adult disability in the United States. Substantial evidence from both experimental and clinical studies has demonstrated that social isolation (SI) can increase stroke incidence and impair recovery. Epidemiological studies demonstrate that an increasing number of patients are living alone, and as the aging population increases, loneliness will only increase in prevalence. SI is increasingly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 96 publications
1
21
0
Order By: Relevance
“…Language itself might have evolved as a vehicle to facilitate social demands 17 . Pathologically, the socially isolated brain has been shown to have higher baseline vascular resistance, lower inflammatory control, and decreased neurogenesis after injury 2123 . These effects of social isolation on the brain are accompanied by a host of systemic physiological changes, including an elevated stress response, inflammation, and hypertension 24 .…”
mentioning
confidence: 99%
“…Language itself might have evolved as a vehicle to facilitate social demands 17 . Pathologically, the socially isolated brain has been shown to have higher baseline vascular resistance, lower inflammatory control, and decreased neurogenesis after injury 2123 . These effects of social isolation on the brain are accompanied by a host of systemic physiological changes, including an elevated stress response, inflammation, and hypertension 24 .…”
mentioning
confidence: 99%
“…Some studies 27,32,42 have indicated that social isolation and social support most likely influence recovery in stroke patients. Our findings also show that social risk is associated with worse recovery.…”
mentioning
confidence: 99%
“…2 Similarly, Venna et al found that clinical data from group-housed animals with stroke showed decreased systemic inflammation, elaboration of BDNFs, enhanced neurogenesis, and improved neuroimmune responsiveness which differed significantly from isolated animals. 3 Studies of stroke survivors have reported similar findings. Boden-Albala et al found that individuals experiencing social isolation experienced worse poststroke outcomes such as death, recurrent stroke, or myocardial infarction.…”
mentioning
confidence: 66%
“…5 The exact mechanism by which social networks influence stroke recovery is not clearly understood, as it is unclear if it is the type, function, density, or frequency of contacts within the social network structure that is most critical to stroke recovery. 3 Aphasia is a poststroke condition where social networks appear critical to recovery. Recent estimates suggest that approximately 18% of individuals with a diagnosis of stroke are discharged from U.S. hospitals with aphasia 6 and there are believed to be more than 2.5 million Americans currently living with aphasia.…”
mentioning
confidence: 99%